2015
DOI: 10.2147/ijn.s90104
|View full text |Cite
|
Sign up to set email alerts
|

Sequential delivery of an anticancer drug and combined immunomodulatory nanoparticles for efficient chemoimmunotherapy

Abstract: Chemoimmunotherapy combines chemotherapy based on anticancer drugs with immunotherapy based on immune activators to eliminate or inhibit the growth of cancer cells. In this study, water-insoluble paclitaxel (PTX) was dispersed in water using hyaluronic acid (HA) to generate a tumor-associated antigen in the tumor microenvironment. Cytosine–phosphate–guanosine oligodeoxynucleotides (CpG ODNs) were used to enhance the T helper (Th) 1 immune response. However, CpG ODNs also induced the secretion of interleukin-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 41 publications
1
6
0
1
Order By: Relevance
“…Our findings are consistent with those of other groups, who have reported the benefits of NPs for delivery of chemotherapy and non-specific innate immunotherapy 41-44. For instance, Roy et al and Heo et al treated murine B16 melanoma tumors with PLGA NPs containing paclitaxel and either a TLR4 or a TLR9 agonist, respectively 41,43. The authors observed an initial delay in tumor growth and a significant influx of lymphocytes into the tumors.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with those of other groups, who have reported the benefits of NPs for delivery of chemotherapy and non-specific innate immunotherapy 41-44. For instance, Roy et al and Heo et al treated murine B16 melanoma tumors with PLGA NPs containing paclitaxel and either a TLR4 or a TLR9 agonist, respectively 41,43. The authors observed an initial delay in tumor growth and a significant influx of lymphocytes into the tumors.…”
Section: Discussionsupporting
confidence: 92%
“…And poly (lactic-co-glycolic acid) (PLGA) is a good choice for a drug delivery vehicle because of its biocompatibility and safety. Moreover, several studies have demonstrated that dyes-loaded or drug-loaded PLGA nanoparticles can induce PDT/SDT or enhance cytotoxicity (McEwan et al., 2014 ; Heo et al., 2015 ; Pakulska et al., 2016 ; Abou-ElNaga et al., 2017 ). Herein, our ideal drug delivery platform is based on PLGA, which has the following advantages: (1) high drug loading efficiency; (2) PTX-based chemotherapy combined with ICG-based PDST; (3) oxygen carried PFC improve hypoxia of tumor (McEwan et al., 2015 ; McEwan et al., 2016 ); (4) controlled drug release.…”
Section: Introductionmentioning
confidence: 99%
“…One is that immunotherapeutic agent can be delivered in appropriate NPs, and the chemotherapy drug was administered in free form. Yong Taik Lim et al have designed two poly(lactic-co-glycolic acid) (PLGA) NPs combined with chemotherapy drug paclitaxel (PTX), one is CpG-loaded PLGA NPs (PCNs) to activate BMDCs, the other is IL-10 small interfering RNA-loaded PLGA NPs (PINs) to silence IL-10 [96]. The treatment of PTX followed by PCNs and PINs could enhance antitumor effect and increase survival rate in B16-F10-bearing melanoma mice compare to PTX alone (p < 0.05).…”
Section: Nanocarriers For Cancer Chemoimmunotherapymentioning
confidence: 99%